É tempo de pipa: a representação da infância em Cidade de Deus, de Paulo Lins, e Lembrancinha do Adeus, de Júlio Ludemir - Anderson Luís Nunes da Mata (Estudos de Literatura Brasileira Contemporânea)
Traditionally understood as an age of innocence and learning, childhood has been shown indifferent colors in the so called "slum" narratives. Thus, poor children, who live in the urban peripheral areas, are represented in fiction as a counterface for such traditional notion of childhood. Lembrancinha do Adeus, by Julio Ludemir, and Cidade de Deus, by Paulo Lins, are both novels built upon characters who maintain only remains of childhood, which indicates both a new sociability for such children and deeper social changes.